2021
DOI: 10.3390/genes12070971
|View full text |Cite
|
Sign up to set email alerts
|

Direct Measurement of B Lymphocyte Gene Expression Biomarkers in Peripheral Blood Transcriptomics Enables Early Prediction of Vaccine Seroconversion

Abstract: Peripheral blood transcriptome is a highly promising area for biomarker development. However, transcript abundances (TA) in these cell mixture samples are confounded by proportions of the component leukocyte subpopulations. This poses a challenge to clinical applications, as the cell of origin of any change in TA is not known without prior cell separation procedure. We developed a framework to develop a cell-type informative TA biomarkers which enable determination of TA of a single cell-type (B lymphocytes) d… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…The plasmatic levels of this protein are markedly elevated in septic patients, and it has been considered a therapeutic target for attenuating inflammatory responses 91 . Additionally, it was shown that TXND5 is hyper-expressed in B cells after COVID-19 vaccination, being a marker for seroconversion 92 . Therefore, the three genes are potential candidates for monitoring disease severity in COVID-19.…”
Section: Resultsmentioning
confidence: 99%
“…The plasmatic levels of this protein are markedly elevated in septic patients, and it has been considered a therapeutic target for attenuating inflammatory responses 91 . Additionally, it was shown that TXND5 is hyper-expressed in B cells after COVID-19 vaccination, being a marker for seroconversion 92 . Therefore, the three genes are potential candidates for monitoring disease severity in COVID-19.…”
Section: Resultsmentioning
confidence: 99%
“…Secondly, outlier samples (i.e. individuals in pseudobulks) were excluded based on Mahalanobis distance metrics that were computed using 19 selected housekeeping genes ( 39 41 ). Finally, for datasets with batches (e.g.…”
Section: Methodsmentioning
confidence: 99%
“…Atorvastatin inhibits ROS production and Nox2 activity by promoting the membrane translocation of TXNDC5 in lipid rafts and enhancing the colocalization of TXNDC5 and Nox2, thus exerting antioxidant effects ( 162 ). Moreover, direct B lymphocyte LS-TA of TXNDC5 is an early biomarker of vaccine response in novel coronavirus pneumonia (COVID-19) ( 163 ).…”
Section: The Role Of Txndc5 In Other Diseasesmentioning
confidence: 99%